Microbiology for Allied Health Students - Smith, Molly; Selby, Sara; Open Textbook Library (Open Textbook Library, 2017)
Microbiology for Allied Health Students is designed to cover the scope and sequence requirements for the single semester Microbiology course for non-majors and allied health students. The book presents the core concepts of microbiology with a focus on applications for careers in allied health. The pedagogical features of Microbiology for Allied Health Students make the material interesting and accessible to students while maintaining the career-application focus and scientific rigor inherent in the subject matter. The scope and sequence of Microbiology for Allied Health Students has been developed and vetted with input from numerous instructors at institutions across the U.S. It is designed to meet the needs of most microbiology courses allied health students. With these objectives in mind, the content of this textbook has been arranged in a logical progression from fundamental to more advanced concepts. The opening chapters present an overview of the discipline, with individual chapters focusing on cellular biology as well as each of the different types of microorganisms and the various means by which we can control and combat microbial growth. The focus turns to microbial pathogenicity, emphasizing how interactions between microbes and the human immune system contribute to human health and disease. The last several chapters of the text provide a survey of medical microbiology, presenting the characteristics of microbial diseases organized by body system.
Chapter 1: An Invisible World -- Chapter 2: The Cell -- Chapter 3: The Eukaryotes of Microbiology -- Chapter 4: Acellular Pathogens -- Chapter 5: Microbial Mechanisms of Pathogenicity -- Chapter 6: Innate Nonspecific Host Defenses -- Chapter 7: Adaptive Specific Host Defenses -- Chapter 8: Diseases of the Immune System -- Chapter 9: Control of Microbial Growth -- Chapter 10: Antimicrobial Drugs -- Chapter 11: Disease and Epidemiology -- Chapter 12: Skin and Eye Infections -- Chapter 13: Respiratory System Infections -- Chapter 14: Urogenital System Infections -- Chapter 15: Digestive System Infections -- Chapter 16: Circulatory and Lymphatic System Infections -- Chapter 17: Nervous System Infections -- Chapter 18: Mechanisms of Microbial Genetics -- Appendix A: Fundamentals of Physics and Chemistry Important to Microbiology -- Appendix B: Mathematical Basics -- Appendix C: Glossary
In English.
Description based on online resource
Keywords: Science -- Textbooks; Biology -- Textbooks